Reality and fiction in US TV series: Lost, CSI and The West Wing. Narrative strategies and verosimilitude - Rovirosa, Anna Tous (Contemporanea, 2011)
The purpose of this paper is to present a methodology of analysis of TV series, taking into account the use of reality and fiction in the narrative construction of these series, as well as the use of verosimilitude in ‘real-world’ series. With the methodology chosen, the purpose is to distinguish between the usage of reality and fiction, on one hand, and the usage of thematic recurrence, myth and metaTV references, on the other. The methodology consists of the edition of televisual text. For, inasmuch as we consider that drama series are a text, they can be edited. The empirical analysis deals with three US TV series: Lost, ABC: 2004-, CSI: Crime Scene Investigation, CBS: 2000- and The West Wing, NBC: 1999-2006. They all belong to the drama’s era, but each of them represents a specific subgenre: adventures and science-fiction, crime and forensic, and workplace and politics.